(untitled) (Bangladesh Pharmaceutical Journal, 2020)
The fruits of Stixis suaveolens (Roxb.) have been a popular folk medicine among traditional practitioners. However, there are questions about its traditional uses due to lack of scientific evidence. This study was aimed to evaluate the effects of crude methanol extract of fruits of S. suaveolens in mice model. The central and peripheral analgesic activity were evaluated using the ‘tail flick’ and ‘writhing’ assay respectively. The anti-hyperglycemic potential was assessed by the ability of the crude extract in reducing blood glucose level in mice after oral administration of glucose. Oral administration (400 mg/kg bw) of the extract showed significant (p<0.001) delay in pain sensation and inhibition of acetic acid induced writhing response in mice model. The results were compared with the respective standard morphine (2 mg/kg bw) and diclofenac (50 mg/kg bw). Likewise, in anti-hyperglycemic assay, maximum reduction (p<0.001) of blood glucose level (39.6%) was observed 120 min after oral intake (400 mg/kg bw) of the extract as compared that exhibited by the standard drug, glibenclamide (46.83%). The in vivo bioassays confirmed that the crude methanolic extract of fruits of S. suaveolens possesses significant central- and peripheral-analgesic as well as anti-hyperglycemic activities. These findings justify its popularity as a traditional medicine and hence demands future study involving isolation and characterization of its bioactive compounds. Bangladesh Pharmaceutical Journal 23(2): 135-140, 2020